Anti-inflammatories and analgesics in pediatric dentistry - Irina Lupse; Alexandrina Muntean; Ioana-Andreea Chis; Anca-Ioana Daniliuc; Mircea Ghergie (Amaltea Medical Publishing House, 2021)
Analgesics are used to reduce pain, which is the main symptom experienced in dental inflammatory pathologies. Painkillers are among the most used drugs in dentistry, along with anti-inflammatories and antibiotics. A lack of knowledge regarding well-defined prescription protocols has been observed. The aim of this study was to revise and update the prescription of anti-inflammatories and analgesics according to the latest guidelines. We performed electronic research of selected databases: PubMed, Google Scholar, AAPD, from 2010-2020, in order to identify the most frequent anti-inflammatories and analgesics used in pediatric dentistry. Approximately 25% of all adverse drug reactions are the consequences of treatments with anti-inflammatory drugs. This paper focuses on both the correct and wrong prescription of medication in pediatric dentistry, as well as on the short and long-term side-effects of this prescription.